Rereading Marx in the Age of Digital Capitalism - Fuchs, Christian (Pluto Press, 2019)
The 'end of history' has not taken place. Ideological and economic crisis and the status quo of neoliberal capitalism since 2008 demand a renewed engagement with Marx. But if we are to effectively resist capitalism we must truly understand Marx: Marxism today must theorise how communication technologies, media representation and digitalisation have come to define contemporary capitalism. There is an urgent need for critical, Marxian-inspired knowledge as a foundation for changing the world and the way we communicate from digital capitalism towards communicative socialism and digital communism.Rereading Marx in the Age of Digital Capitalism does exactly this. Delving into Marx's most influential works, such as Capital, The Grundrisse, Economic and Philosophic Manuscripts, The German Ideology and The Communist Manifesto, Christian Fuchs draws out Marx's concepts of machinery, technology, communication and ideology, all of which anticipate major themes of the digital age.A concise and coherent work of Marxist media and communication theory, the book ultimately demonstrates the relevance of Marx to an age of digital and communicative capitalism.